Penarapan Fungsi Partai Politik sebagai Sarana Rekrutmen Politik pada PKS DPRD Sumatera Utara - Shintya Monica Hasibuan; Via Avinka Valentina; Riska Adelina Nasution; Zulhazmi Maulana; Elly Warnisyah (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Political recruitment is regulated in article 11 paragraph 1 of Law No. 2 of 2008 concerning political parties which states that one of the functions of political parties is as a means of political recruitment in the process of filling political positions through a mechanism that takes into account gender equality and justice. The aim of this research is to find out how the Prosperous Justice Party (PKS) performs its function as a place for political recruitment in delivering for every member of the public who wants to occupy government positions or as party administrators by going through the stages of selection from the aspect of political recruitment. The process of writing this is by applying qualitative methods with secondary data sourced from previous research journals. Members are the most important factor in political parties, they function to market political parties to the public. In addition, cadres conduct party education to the community, and empower the community to understand the importance of politics in the life of the state. Currently, many people do not understand the role and importance of political parties in government. Meanwhile, the position and function of political parties in government is very important so that qualified and integrity cadres are needed to lead Indonesia. Keywords: Political Parties, Prosperous Justice Party, Political Recruitment